In Memoriam: Jose V. Abueva and Vicente D. Mariano - Editors, PJPA (Philippine Journal of Public Administration; Vol 65 No 1&2 (2021), 2021)
This issue of the Philippine Journal of Public Administration (PJPA) is dedicated to the memory of Jose V. Abueva and Vicente R. Mariano, two pillars of the Philippine Journal of Public Administration (PJPA) who passed away on 18 August 2021 and 27 April 2021, respectively.